GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Dual Effects of a Bothrops asper Phospholipase A₂: Anti-Vibrio Properties and Shrimp Hemocyte Cytotoxicity - Ricardo S. P. Patiño; David Salazar-Valenzuela; Bruno Mendes; Kathya Bustamante; Josselin A. Hernández-Altamirano; Cecilia Tomalá; Cristobal Domínguez-Borbor; Josselyn A. Ortega-Pila; Fernanda Toscano; Marbel Torres Arias; Jenny Rodríguez; José Rafael de Almeida (Probiotics and Antimicrobial Proteins, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Upregulation of NLRP3 Inflammasome in Specific Hippocampal Regions: Strengthening the Link Between Neuroinflammation and Selective Vulnerability in Alzheimer’s Disease - Eliana C. B. Toscano; Alberto F. O. Justo; Michelle C. A. Paula; Laura B. Grossi; Vitor H. Neves; Renata E. P. Leite; Vitor R. Paes; Rossana C. N. Melo; Ricardo Nitrini; Carlos Pasqualucci; Eduardo Ferriolli; Antonio L. Teixeira; et al. (Molecular Neurobiology, 2025)

Integrating UAV hyperspectral imaging with machine learning techniques to predict tomato ecophysiological parameters and yield - A. Matese; N. Hamie; S. Baronti; A. Berton; R. Dainelli; P. Toscano; F. Ugolini; S. F. Di Gennaro (Precision Agriculture, 2025)

Assessing multiple benefits of people‐centered biocultural restoration - Hudson Toscano da Silva; Felipe P. L. Melo; Gabriel da Costa Ferreira; Cristina Baldauf (Conservation Biology, 2025)
Restoration is currently among the most important tools for conserving biodiversity, but participation in restoration by local communities in its planning and design must be improved. We devised a people‐centered biocultural approach to restoration that combines Indigenous local knowledge and scientific methods to select species for restoration such that human welfare and biodiversity conservation are considered. We applied the approach to the Caatinga dry forest, for which we simulated agroforestry productive systems based on plant species previously selected by locals for use in restoration, given their importance for water, energy, and food security. We compared functional diversity in the simulated systems with functional diversity in natural systems. Common native and some non‐native species with low invasive potential dominated the average productive system. These species had functional diversity similar to that of natural vegetation but had a slightly different functional profile. Simulated systems were dominated by plant species with more acquisitive functional strategies than native flora. The adoption of our biocultural approach to restoration programs in the region illustrates the importance of local participation; local selection of species for restoration had little effect on ecosystem functional diversity. Our framework can be readily adapted to various contexts for evaluating cultural preferences and the ecological efficacy of biocultural restoration initiatives globally.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Coastal raptors and raiders: New bird tracks in the Pleistocene of SW iberian Peninsula - Carlos Neto de Carvalho; João Belo; Silvério Figueiredo; Pedro P. Cunha; Fernando Muñiz; Zain Belaústegui; Mário Cachão; Joaquín Rodriguez-Vidal; Luis M. Cáceres; Andrea Baucon; Andrew S. Murray; Jan-Pieter Buylaert; et al. (Quaternary Science Reviews, 2023)

Hyperphosphorylated Tau in Mesial Temporal Lobe Epilepsy: a Neuropathological and Cognitive Study - Eliana C. B. Toscano; Érica L. M. Vieira; Lea T. Grinberg; Natalia P. Rocha; Joseane A. S. Brant; Regina S. Paradela; Alexandre V. Giannetti; Claudia K. Suemoto; Renata E. P. Leite; Ricardo Nitrini; Milene A. Rachid; Antonio L. Teixeira (Molecular Neurobiology, 2023)

Estimating EEG Source Dipole Orientation Based on Singular-value Decomposition for Connectivity Analysis - M. Rubega; M. Carboni; M. Seeber; D. Pascucci; S. Tourbier; G. Toscano; P. Van Mierlo; P. Hagmann; G. Plomp; S. Vulliemoz; C. M. Michel (Brain Topography, 2019)

Carbon sequestration capacity and productivity responses of Mediterranean olive groves under future climates and management options - L. Brilli; E. Lugato; M. Moriondo; B. Gioli; P. Toscano; A. Zaldei; L. Leolini; C. Cantini; G. Caruso; R. Gucci; P. Merante; C. Dibari; et al. (Mitigation and Adaptation Strategies for Global Change, 2019)

An assessment of contamination of the Fusaro Lagoon (Campania Province, southern Italy) by trace metals - M. Arienzo; F. Toscano; M. Di Fraia; L. Caputi; P. Sordino; M. Guida; F. Aliberti; L. Ferrara (Environmental Monitoring and Assessment, 2014)

Freshwater ostracods as environmental tracers - F. Ruiz; M. Abad; A. M. Bodergat; P. Carbonel; J. Rodríguez-Lázaro; M. L. González-Regalado; A. Toscano; E. X. García; J. Prenda (International Journal of Environmental Science and Technology, 2013)

New Mediterranean Biodiversity Records (December 2012) - M. THESSALOU-LEGAKI; O. AYDOGAN; P. BEKAS; G. BILGE; Y.O. BOYACI; E. BRUNELLI; V. CIRCOSTA; F. CROCETTA; F. DURUCAN; M. ERDEM; A. ERGOLAVOU; H. FILIZ; et al. (Mediterranean Marine Science, 2012)
This paper presents records extending or confirming the distribution of Mediterranean species. Three alien algae are included, namely Codium taylorii reported for the first time from the Aegean and Turkey (Izmir Gulf), Caulerpa racemosa var. cylindracea (Karpathos and Chalki Isl., Aegean Sea) and Ganonema farinosum (Karpathos Isl., Aegean Sea). As far as animals are concerned, Litarachna divergens (Acari: Hydrachnidia) was recorded (Side, Eastern Mediterranean) and represents a new amendment at genus level for Turkish fauna. Other invertebrates include alien species such as the crabs Dyspanopeus sayi (Lago Fusaro, SW Italy), Percnon gibbesi (Larnaca, Cyprus; Karpathos and Chalki Isl., Aegean Sea) and Callinectes sapidus (Voda estuary, NW Greece), the nudibranch Aplysia dactylomela (Boka Kotorska Bay, Montenegro), the gastropod Conomurex persicus (Karpathos and ChalkiIsl., Aegean Sea) and the bryozoan Electra tenella (Livorno harbour and Messina Straits area). The alien fish Siganus luridus, Siganus rivulatus, Fistularia commersonii, Sphyraena chrysotaenia and Sargocentron rubrum are also reported from the islands of Karpathos and Chalki, and Pteragogus pelycus from Heraklion Bay, Crete. In addition, new localities for four rare Mediterranean inhabitants are given: the cephalopod Thysanoteuthis rhombus (NW Sardinia) and the fish: Lampris guttatus (Calabria, S Italy), Petromyzon marinus (Gokova Bay) and Remora australis (Saronikos Gulf), while the opisthobranch gastropod Cerberilla bernadettae is reported for the first time from the E Mediterranean (Cyprus). Finally, three species of the Aegean ascidiofauna are recorded for the first time: Lissoclinum perforatum, Ciona roulei and Ecteinascidia turbinata. Furthermore, it was established that Phallusia nigra has extended its distributional range to the north of the Aegean Sea.

The demise of a major Acropora palmata bank–barrier reef off the southeast coast of Barbados, West Indies - I. G. Macintyre; P. W. Glynn; M. A. Toscano (Coral Reefs, 2007)

Severe Disseminated Tuberculosis After Intravesical Instillation of Bacillus Calmette-Gurin - R. Proena; M. Toscano Rico; O. Cardoso; C. Salvado; P. Rodrigues; J. Machado (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

El Niño related coral bleaching in Palau, Western Caroline Islands - J. Bruno; C. Siddon; J. Witman; P. Colin; M. Toscano (Coral Reefs, 2001)